ANALISIS MENGENAI SINGKRONISASI LEMBAGA PEMASYARAKATAN SEBAGAI PENGGANTI PIDANA PENJARA - Rusliyadi, Hendra; Dharma Laksana, I Gusti Ngurah (Kertha Wicara : Journal Ilmu Hukum; Vol. 04, No. 01, Februari 2015, 2015)
Imprisonment is a punishment that often given to the criminals, but imprisonment is not have a detterent effect to the criminals. Different case with the concept of a correctional institution that seeks to educate the inmates. This research uses the juridical normative method, due to the conflict norms between of the Criminal Code by Act No. 12 of 1995 about Penitentiary. In terminology terms, imprisonment can be interpreted as a criminal seizure of independence. However, the concept is incompatible with the purpose of sentencing. On the other side, the correctional institution established to educate inmates. When they are out of the penitentiary, they have the skills and can live in a society very well. Therefore, it can be concluded that the concept of correctional institution is accordance with the purposes of the punishment is more concerned with the making process of the inmates.
Keywords: ANALISIS MENGENAI SINGKRONISASI LEMBAGA PEMASYARAKATAN SEBAGAI PENGGANTI PIDANA PENJARA